Precautionary measures and the principle of reasoned persuasion (Revista do Tribunal Regional Federal da 3ª Região, 2011)
“Justice is a feeling that in its abstraction encompasses harmony, symmetry and equity. Ihering was very happy to compare the feeling of justice to the feeling of love, stating that its strength lies in feeling. Regarding the feeling that an injustice brings, he says that 'those who have never felt this pain, in themselves or in others, have not yet understood what law is, even if they know the entire corpus juris by heart. It is not reasoning, but only feeling that can give us this understanding, and it is for this very reason that the feeling of justice is often rightly referred to as the primordial psychological source of law'."(*) Thus, there is no doubt that Law no. 12. 403, of May 4, 2011, has brought about a profound transformation with regard to imprisonment and pre-trial release, since it makes pre-trial release, in accordance with Constitutional Criminal Procedure Law, the institute of the ultima ratio for the curtailment of the ambulatory freedom of someone who has violated an incriminating criminal rule. It is true that the new law included numerous alternatives, such as precautionary measures, other than imprisonment, as prescribed in articles 319 and 320 of the Code of Criminal Procedure.
Keywords: precautionary measures; motivaded reasoning; imprisonment; provisional release